Telemedicine for under-resourced patients with systemic lupus erythematosus: a qualitative study exploring the views and experiences of patients and their healthcare team - Bowman, Savannah; Agarwal, Sandeep K.; Ferguson, Keshia C.; Maliekel, Maryjo J.; Lopez-Olivo, Maria A.; Suarez-Almazor, Maria E.; Danila, Maria I.; Yazdany, Jinoos; Bruera, Sebastian (Frontiers in Health Services, 2025)
ObjectivesThere is scarce knowledge on the benefits, limitations, and acceptance of telemedicine in patients with systemic lupus erythematosus (SLE), particularly in those from under-resourced groups. We aimed to assess the experiences and views on telemedicine of people with SLE, clinicians, and nursing staff from a safety net healthcare system in Harris County, Texas, defined as a hospital network that primarily serves low-income, uninsured, and vulnerable populations.MethodsWe conducted semi-structured 1:1 in-person interviews of patients with SLE and their clinical team members, in Harris County, Texas. Using Levesque's conceptual framework for healthcare access, semi-structured interviews and content analysis were used to explore benefits and limitations of telemedicine in under-resourced patients with SLE. Interview content was coded using inductive and deductive approaches. Data collected proceeded until thematic saturation was reached. Themes and subthemes were identified and visualized.ResultsFourteen interviews were conducted. The participants included six patients with SLE, three rheumatologists, two nurses, two medical assistants, and one rheumatology fellow. All participants had previously participated in telemedicine visits. One hundred and fifty-one codes were identified. Five key themes emerged from the analysis, including: (1) Access and Convenience, (2) Technological and Linguistic Barriers, (3) Economic Considerations, (4) Quality of Care and Disease Outcomes, and (5) Implementation of Telemedicine. Analysis showed that telemedicine could improve access to care and adherence to clinic visits by reducing the barriers associated with socioeconomic factors. On the other hand, barriers to telemedicine included digital literacy, concern about negative impact on physician-patient relationship, and language discordance.ConclusionThere is an opportunity to improve access to care in patients with SLE, particularly from under-resourced backgrounds, by leveraging the benefits of telemedicine with respect to access to care, while addressing the barriers to successful implementation.